Performance Analysis of High Voltage Insulators Surface Condition Using Time-frequency Distribution - sulaiman, azhar; Abdullah, Abdul Rahim; Aman , Aminudin; NORDDIN, NURBAHIRAH; Zainal Abidin, Nur Qamarina (2013)
This paper presents the leakage current of polymeric and non–polymeric insulation materials in contaminated condition. High Density Polyethylene (HDPE) and Polypropylene (PP) are selected as polymeric materials. Meanwhile, glass is selected as non-polymeric material. The purpose of this study is to identify performance of insulator surface condition against its tracking and erosion and grouped according to the shapes of leakage current waveform. By using Incline Plane Tracking (IPT) test method for evaluating resistance to tracking and erosion is complying with BS EN 60587-2007. The result of leakage current waveforms were captured and recorded in continuous duration time. From that result, monitoring signal output will analyze using Time- Frequency Distribution (TFD). Spectrogram is used as a diagnostic tool to analysis time-frequency representation (TFR). Although, the harmonic components for polymeric and non-polymeric material can be define by Spectrogram. TFR result also will estimate to identify the signal characteristic patterns of the materials.